New development : Complexity-informed interpretation of social innovation - Jalonen, Harri (Taylor & Francis, 2021)
Social innovation is a systemic and complex process aiming at achieving added value for the whole society. This article explores the applicability of complexity thinking as a useful resource for conceptualizing social innovation. The author advances the complexity-informed research tradition by emphasizing the emergence of social innovation and addressing the paradox of being in charge but not in control. By drawing on such concepts as emergence, self-organization, diversity, co-evolution, feedback processes, dissipative structures and attractors, the article proposes a new approach to cope with the complexities of social innovation.
Keywords: Complexity thinking; emergence; wicked game; wicked problems; social innovations; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|